A feedback loop between dynamin and actin recruitment during clathrin-mediated endocytosis. - Marcus J Taylor; Marko Lampe; Christien J Merrifield (PLoS Biology)
Clathrin-mediated endocytosis proceeds by a sequential series of reactions catalyzed by discrete sets of protein machinery. The final reaction in clathrin-mediated endocytosis is membrane scission, which is mediated by the large guanosine triophosphate hydrolase (GTPase) dynamin and which may involve the actin-dependent recruitment of N-terminal containing BIN/Amphiphysin/RVS domain containing (N-BAR) proteins. Optical microscopy has revealed a detailed picture of when and where particular protein types are recruited in the ∼20-30 s preceding scission. Nevertheless, the regulatory mechanisms and functions that underpin protein recruitment are not well understood. Here we used an optical assay to investigate the coordination and interdependencies between the recruitment of dynamin, the actin cytoskeleton, and N-BAR proteins to individual clathrin-mediated endocytic scission events. These measurements revealed that a feedback loop exists between dynamin and actin at sites of membrane scission. The kinetics of dynamin, actin, and N-BAR protein recruitment were modulated by dynamin GTPase activity. Conversely, acute ablation of actin dynamics using latrunculin-B led to a ∼50% decrease in the incidence of scission, an ∼50% decrease in the amplitude of dynamin recruitment, and abolished actin and N-BAR recruitment to scission events. Collectively these data suggest that dynamin, actin, and N-BAR proteins work cooperatively to efficiently catalyze membrane scission. Dynamin controls its own recruitment to scission events by modulating the kinetics of actin and N-BAR recruitment to sites of scission. Conversely actin serves as a dynamic scaffold that concentrates dynamin and N-BAR proteins at sites of scission.